Pengembangan Ensiklopedia Tumbuhan Obat di Distrik Manokwari Barat Sebagai Sumber Belajar Materi Kingdom Plantae Siswa Kelas X SMA Advent Kabupaten Manokwari - Baharuddin, Wiska; Maturahmah, Enik (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the validity, practicality and effectiveness of the development of an encyclopedia book as a learning resource for biology for class X SMA Advent Manokwari, Manokwari Regency. This encyclopedia is designed based on the results of an inventory of medicinal plants found in West Manokwari District, integrating local wisdom and scientific knowledge to improve students' understanding of biodiversity and the use of medicinal plants contextually. The method used in this study is the Research and Development (R&D) method by adapting the 4D development model, namely Define, Design, Development and Disseminate. The steps in this research include observing the types of medicinal plants in West Manokwari District (seeing, documenting, and identifying which are then made into an encyclopedia), product design, and product validation. Validation of the encyclopedia product was carried out by material experts and media experts who evaluated aspects of content, format, and readability to ensure its feasibility and effectiveness as a learning resource. Based on the results of the validation analysis by expert validators, it is known that the results of the validation of the encyclopedia book obtained an average value of 4.55 from the validator and were declared valid, validation by biology teachers had a percentage of 95.6% and it can be concluded that the category is very suitable for use as a source of learning biology and is also practical. In the field trial in this case students, the validation results had a percentage of 94%, this shows that the medicinal plant encyclopedia book is very suitable for use as a learning resource for students.